Pendekatan Multidisiplin dalam Pencegahan dan Penanganan Masalah Narkoba di Indonesia: Sinergi antara Hukum, Psikologi, dan Kesehatan Masyarakat - Fakhlur; Pamungkas, Bernadus Dimas Galih; Fathinnuddin, Muhammad (HUMANIORUM, 2024)
Drug abuse has become an urgent global issue, and Indonesia, like many other countries, is not exempt from facing this challenge. This issue has significant impacts on various aspects of community life, ranging from social, and economic, to health. Although the government has implemented various strict regulations and sanctions, as outlined in Law Number 35 of 2009, challenges in eradicating drug abuse remain and evolve. This article investigates the multidisciplinary approach to addressing drug-related issues, emphasizing the importance of synergy between law, psychology, and public health. Through an in-depth study of literature, regulations, and recent data, this research reveals an urgent need for a more inclusive and comprehensive strategy. This strategy must consider the issue's complexity, the addictive nature of drugs, and the social and health implications arising from their misuse. By integrating a firm legal approach, a psychological understanding of the causes and impacts of drug abuse, and an inclusive public health approach, it is hoped that Indonesia can formulate more effective and sustainable solutions to face the challenges of drugs in the future.